Antibiotic Treatment in Native Valve Infective Endocarditis - Garcia-Borbolla, Rafael; Garcia-Borbolla, Mariano (Infectious Disorders - Drug Targets, 2010)
Previous to the availability of antimicrobial therapy, infective endocarditis (IE) was habitually lethal. Although approximately 80 percent of patients with endocarditis currently survive their infections, one of every six patients with IE does not survive the initial hospitalization, and up to one-third of patients infected with highly virulent organisms (such as Staphylococcus aureus) may die as a direct or indirect result of their valvular infection. An unfavourable outcome in these patients can occur despite having received appropriate antimicrobial therapy in a suitable approach, and despite the expert use of modern diagnostic techniques. Our purpose is to review the main issues related to the antimicrobial therapy.
Keywords: microorganisms